Andropause – State of the art 2015 and review of selected aspects - Jakiel, Grzegorz; Makara-Studzińska, Marta; Ciebiera, Michał; Słabuszewska-Jóźwiak, Aneta (Menopause Review/Przegląd Menopauzalny, 2015)
The term ‘male menopause’ was first used in 1944 to describe various complaints of ageing men which at least partially mirrored the climacteric symptoms in women. Continuous research resulted in the evolution of opinions about the nature of these complaints, from the clinical syndrome, diagnosed with the use of disease-targeted questionnaires, to a well-defined clinical and biochemical syndrome. The pathophysiological causes – gonad ageing (with a compensatory rise in luteinizing hormone), age-related increase in serum sex hormone-binding globulin (SHBG) levels, the role of visceral adipose tissue as a place for aromatization of androgen to estrogen, and lower sensitivity of testosterone receptors – have been described. However, no consensus was reached as far as the definition, incidence, treatment, and especially testosterone therapy, are concerned. Our review presents the current standpoints, indicating the predictive role of late-onset hypogonadism (LOH) in evaluating male health as well as the current literature reports on the risks and benefits of using testosterone therapy.